2023
DOI: 10.3390/su15065350
|View full text |Cite
|
Sign up to set email alerts
|

Study on Internal Flow Characteristics of Hydrocyclone with Guide Vanes

Abstract: Hydrocyclone with guide vanes is one type of swirl flow launching device without energy input. For researching the flow characteristics of that hydrocyclone, the flow distribution of the sections and their variation along the flow were studied using numerical simulation and physical experiment. In addition, the flow field was convenient to be divided into three-dimensional velocities: axial velocity, circumferential velocity, radial velocity and the static pressure. The result showed that the water flow had ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The CFD method has been extensively applied to the optimization design of hydrocyclones to study internal flow fields and particle micromotion characteristics, with the advantages of accuracy, high efficiency, and short duration [32,33]. For the numerical simulation of hydrocyclones, multiphase models commonly utilize the VOF model, mixture model, and Eulerian model, while turbulence models include RSM and LES models; the DPM is used to track particle trajectories [34][35][36]. Durango-Cogollo et al [37] reported that the RSM and LES models have higher computational accuracy than the k-ε model, but the RSM has faster computational efficiency and lower mesh quality requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The CFD method has been extensively applied to the optimization design of hydrocyclones to study internal flow fields and particle micromotion characteristics, with the advantages of accuracy, high efficiency, and short duration [32,33]. For the numerical simulation of hydrocyclones, multiphase models commonly utilize the VOF model, mixture model, and Eulerian model, while turbulence models include RSM and LES models; the DPM is used to track particle trajectories [34][35][36]. Durango-Cogollo et al [37] reported that the RSM and LES models have higher computational accuracy than the k-ε model, but the RSM has faster computational efficiency and lower mesh quality requirements.…”
Section: Introductionmentioning
confidence: 99%